Interrenal cell zonation in the adrenal gland of the goose (Anser anser) - Gulmez, N; Kocamis, H; Liman, N; Kukner, A (Growth Publishing Co Inc, 2004)
The adrenal medulla in mammalian species is surrounded by a cortex that contains three distinct layers, whereas the cortex and medulla are intermingled in poultry species. The objective of the present study was to determine the distinct zonation changes in the adrenal cortex of geese in various ages using both electron and light microscopy. Adrenal glands were obtained from French Geese (Anser anser) under deep ether anesthesia at posthach day 1, 5, 10, 21 and 30 (n = 5 per day). The cytoplasm of interrenal cells located beneath the adrenal capsule (sub-capsular zone, SCZ) were stained lighter than that of interrenal cells located inside the adrenal gland (inner zone, IZ) and contained several vacuoles for each sampling day. Additionally, unlike IZ cells, SCZ cells contained nuclei that were various shapes and surrounded by irregularly arranged membranes, lipid droplets which were not surrounded by a membrane, mitochondria with mostly shelf-like cristae. The arrangement of SCZ cells appears similar to that of zona glomerulosa and also the arrangement of IZ cells to that of zona fasciculata of mammalian adrenal cortex, suggesting the significant signs of zonation in goose adrenal cortex.
Keywords: adrenal gland; goose; zonation; electron and light microscopy